2014
DOI: 10.7314/apjcp.2014.15.2.647
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lobaplatin in Trans-catheter Arterial Chemoembolization for Primary Hepatic Carcinoma

Abstract: Objective: To explore the efficiency of single application of lobaplatin in tran-scatheter arterial chemoembolization (TACE) for patients with a primary hepatic carcinoma who were unable or unwilling to undergo surgery. Methods: 173 patients with primary hepatic carcinoma diagnosed by imaging or pathology were randomly divided into experimental and control groups and respectively treated with lobaplatin and pirarubicin hydrochloride as chemotherapeutic drugs for TACE. The amount of iodipin was regulated accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Its use, however, is limited by sometimes severe organ toxicity, especially neuro-and nephrotoxicity. Carboplatin shows a favorable spectrum of toxicity, with reversible myelosuppression being the dose-limiting toxicity (Deng et al, 2013;Huang et al, 2013;Peng et al, 2014;Wang et al, 2014;Wu et al, 2014;Zhao et al, 2014). Especially in ovarian cancer, carboplatin appears to have equivalent activity to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Its use, however, is limited by sometimes severe organ toxicity, especially neuro-and nephrotoxicity. Carboplatin shows a favorable spectrum of toxicity, with reversible myelosuppression being the dose-limiting toxicity (Deng et al, 2013;Huang et al, 2013;Peng et al, 2014;Wang et al, 2014;Wu et al, 2014;Zhao et al, 2014). Especially in ovarian cancer, carboplatin appears to have equivalent activity to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of human non-small-cell lung cancer reported that the combination of lobaplatin with paclitaxel shows enhanced activity compared with cisplatin combined with paclitaxel 17 . Lobaplatin has also been shown to exhibit therapeutic efficacy in the treatment of hepatic cancer 18 , 19 , with a total effective rate of 67.6%.…”
Section: Introductionmentioning
confidence: 99%
“…The lower toxicity of LBP has been demonstrated in breast cancer ( 12 ), lung cancer ( 13 ), oesophageal carcinoma ( 14 ), and hepatic cancer ( 15 ). Patients with ESCC after surgery usually have worse PSs than those with other types of cancer.…”
Section: Discussionmentioning
confidence: 99%